THE EUROPEAN NEIGHBOURHOOD POLICY TOWARDS UKRAINE: NO REAL INCENTIVES OF THE HAUNTING SHADOW OF RUSSIA? - Yakovenko, K.; Malova, D. (The Journal of V.N. Karazin Kharkiv National University. Series "Issues of Political Science", 2013)
The ENP is a weakly institutionalized framework for bilateral relations between the European Union and targeting countries. The European Neighbourhood Policy is not a “possible-membership” cooperation policy, therewith being a rather limiting agenda. The relations of the European Union and Ukraine are not bilateral, with Russia emerging as the third party.